Pengendalian Vektor dan Eliminasi Malaria: Literature Review - Ummi Kaltsum; Yuanita Windusari; Hamzah Hasyim (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Malaria is an important tropical parasitic disease in the world, and is still a major health problem. Malaria vector control is one of the efforts to prevent and control malaria which aims to break the chain of transmission of malaria. Vector control includes actions directed against disease vectors, which are intended to limit their ability to transmit disease by protecting areas that are known to be receptive to transmission. Identify opportunities in vector control aspects that can be utilized by the state in an effort to achieve zero malaria cases and achieve elimination certification by 2030. This research method is a descriptive observational study using a literature review design, with the NCBI database. In the elimination phase, the objective of vector control is to reduce the vector capacity of the local vector population below the critical threshold required to maintain transmission. In order to achieve effective vector control towards elimination, among various confounding factors, it is important to identify challenges related to the biological and bionomic character of the vector and associated operational issues.